GENDER MARKING IN SLOVENE AND RUSSIAN ADDRESSING CONSTRUCTIONS (Philological Studies, 2020)
The article discusses the problematic use of the male gender forms, referring to the biological female gender subject. In the Russian language, the usage is standardized, when a noun in a clause carries the attributive function and is, as such, universal. On the other hand, the female gender form is used for the actual referential subject. In Slovene forms of addressing, a male gender form is used when referring to a female subject – the »antiagreeing« phrases Mrs professor and Mrs doctor coexist with the matching (systematical) phrases, where the headword of each nominal phrase ends with a derivational suffix, denoting female gender. The difference between »antiagreement« and the matching phrases lies in the context of addressing and is mainly of stylistic nature. The article shows some options for either strategy and later on focuses on the comparison with a strategy of addressing in the Russian language: the equivalents of the Slovene phrases (Mrs professor, Mrs doctor, and their matching phrases, where the headword of each nominal phrase ends with a derivational suffix, denoting female gender), addressing by the first name and patronym, addressing by the combination Mrs/mr + last/first name and addressing by general terms, aiming for a neutral meaning.
Keywords: gender; agreement; antiagreement; addressing; contrastive analysis